Comparative Analysis of Conventional and Emerging Technologies for Seawater Desalination: Northern Chile as a Case Study - Saavedra-Fenoglio, A; Mahn-Osses, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The aim of this work was to study different desalination technologies as alternatives to conventional reverse osmosis (RO) through a systematic literature review. An expert panel evaluated thermal and membrane processes considering their possible implementation at a pilot plant scale (100 m3/d of purified water) starting from seawater at 20◦C with an average salinity of 34,000 ppm. The desalination plant would be located in the Atacama Region (Chile), where the high solar radiation level justifies an off-grid installation using photovoltaic panels. We classified the collected information about conventional and emerging technologies for seawater desalination, and then an expert panel evaluated these technologies considering five categories: (1) technical characteristics, (2) scale-up potential, (3) temperature effect, (4) electrical supply options, and (5) economic viability. Further, the potential inclusion of graphene oxide and aquaporin-based biomimetic membranes in the desalin-ization processes was analyzed. The comparative analysis lets us conclude that nanomembranes represent a technically and economically competitive alternative versus RO membranes. Therefore, a profitable desalination process should consider nanomembranes, use of an energy recovery system, and mixed energy supply (non-conventional renewable energy + electrical network). This document presents an up-to-date overview of the impact of emerging technologies on desalinated quality water, process costs, productivity, renewable energy use, and separation efficiency. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.